The Effect Of Cow State Fertilizer with Various Bioactivations and Cow Broth Feeding On The Growth and Production Of Soybean (Glycine Max L. Merril). - Siska Melinda; Fiana Podesta (Nabatia, 2021)
The Effect of Cow Manure With Various Bioactivators And Giving Beef Broth To The Growth And Yield Of Soybeans (Glicine Max L. Merril) Supervised by Dwi fitriani, SP. MP and Dr.Ir.Ririn Harini,MP. The purpose of this study was to determine the interaction and effect of cow manure with various bioactivators and broth. This research was conducted in Pondok Kubang District, Central Bengkulu Regency, Bengkulu Province. The design used was a completely randomized design (CRD) factorial treatment 1, namely cow manure with various bioactivators A0 (Control) A1 (Yeast) A2 (Stale Rice) A3 (Rumen). The second treatment was giving control broth, 100 ml/L, 150 ml/L, 200 ml/L. Each treatment was repeated 3 times in order to obtain 48 experimental units by planting 3 plants for each experimental unit to obtain 144 plants. The results showed that the treatment of cow manure with various bioactivators had a significant effect on the parameters of leaf number 56 DAP, number of branches 56 DAP, number of root nodules, number of pithy pods, dry weight of planting, weight of planted seeds, weight of 100 seeds. and has not shown any effect on other parameters.